2016
DOI: 10.1177/0272431615590230
|View full text |Cite
|
Sign up to set email alerts
|

Improving the School Context of Early Adolescence Through Teacher Attunement to Victimization

Abstract: The present study examined the effects of teacher attunement to victimization on student perceptions of the bullying culture of their schools as a means of fostering a sense of belonging among early adolescents. Participants (n = 1,264) in sixth grade reported on the frequency that they had been bullied, and teachers were asked to report students who were “picked on.” Teacher attunement represented the correspondence between self-identified and teacher-identified victims. Attunement at the beginning of the sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 40 publications
3
47
0
2
Order By: Relevance
“…Positive student-teacher relationships can help students achieve, engage, regulate their emotions, build social competence, and take on academic challenges. High-quality teacher-student relationships may also (with other teacher strategies) reduce stereotype threat (Steele, 2010), protect students who are at higher levels of risk for poor outcomes (e.g., Roorda, Koomen, Spilt, & Oort, 2011), and buffer the effects of victimization and other adversity (e.g., Norwalk, Hamm, Farmer, & Barnes, 2016). Together, the neural integration of affective, cognitive, social, and emotional processes that are vital to student motivational states and successful learning reflect the power of these developmentally constitutive relationships, particularly when combined with a well-designed mastery learning framework.…”
Section: Relationships With Teachers and Other Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive student-teacher relationships can help students achieve, engage, regulate their emotions, build social competence, and take on academic challenges. High-quality teacher-student relationships may also (with other teacher strategies) reduce stereotype threat (Steele, 2010), protect students who are at higher levels of risk for poor outcomes (e.g., Roorda, Koomen, Spilt, & Oort, 2011), and buffer the effects of victimization and other adversity (e.g., Norwalk, Hamm, Farmer, & Barnes, 2016). Together, the neural integration of affective, cognitive, social, and emotional processes that are vital to student motivational states and successful learning reflect the power of these developmentally constitutive relationships, particularly when combined with a well-designed mastery learning framework.…”
Section: Relationships With Teachers and Other Adultsmentioning
confidence: 99%
“…Peers socialize each other in the classroom, school, and community through social learning, reference group effects, and peer pressure in dyads and groups (e.g., Snyder, Schrepferman, Bullard, McEachern, & Patterson, 2012). As discussed earlier, teachers and other adults intentionally and unintentionally play a role in structuring peer relationships, and this structuring is affected by their ability to attune to students (Farmer, Lines, & Hamm, 2011;Norwalk et al, 2016). Adults can organize contexts in ways that promote development.…”
Section: Peersmentioning
confidence: 99%
“…Others have measured teacher attunement as teachers' awareness of their students' characteristics and behavior and found that when teachers had high levels of attunement to aggression, the popularity status of highly aggressive boys decreased over time (Ahn & Rodkin, 2014). These findings underscore the impact teacher attunement can have on their students' peer experiences (e.g., Norwalk, Hamm, Farmer, & Barnes, 2015). What is lacking in the teacher attunement literature is whether teachers' perceptions of their students' characteristics are related to how attuned they are.…”
Section: Teacher Attunementmentioning
confidence: 99%
“…To do this, it is important for teachers to be attuned to the social dynamics of the classroom (Norwalk et al, 2015). This involves promoting teachers' knowledge and awareness of classroom leaders, bullies, socially vulnerable students, and the peer groups that make up the social system.…”
Section: Feedback To Promote Positive Dynamicsmentioning
confidence: 99%